Josefa Dussek - Clar, Johann Friedrich August, 1768-1834 (artist):::Creator::::::::::::; Haake:::Contributor:::::::::::: (2021)
Reproduction of engraving by Clar based on a portrait from 1796 by Haake in the Národni Museum, Prague.